2022
DOI: 10.1111/jan.15528
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on help‐seeking behaviours of Indigenous and Black women experiencing intimate partner violence in the United States

Abstract: Aims This article discusses possible barriers to help‐seeking that Indigenous and Black women encountered when seeking help related to experiences of intimate partner violence during the COVID‐19 pandemic. Design This article is focused on understanding the impact of the COVID‐19 pandemic on populations at highest risk for intimate partner violence in its most severe forms. Data Sources Literature sources range from 2010 to 2022. The article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
2
0
5
Order By: Relevance
“…For instance, a 2020 population-based survey in the U.K. found that many individuals who experienced a potential cancer symptom during the pandemic decided not to contact their healthcare provider because of various reasons, including being worried about wasting the doctor's time, not wanting to put a strain on healthcare services on top of the pandemic, or not wanting to make a fuss (Quinn-Scoggins et al, 2021). A similar pattern was also observed in individuals experiencing mental health symptoms and intimate partner violence (Ruiz et al, 2022;Yonemoto & Kawashima, 2022). Future social work research should take into account the impact of the COVID-19 pandemic on individual support seeking.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, a 2020 population-based survey in the U.K. found that many individuals who experienced a potential cancer symptom during the pandemic decided not to contact their healthcare provider because of various reasons, including being worried about wasting the doctor's time, not wanting to put a strain on healthcare services on top of the pandemic, or not wanting to make a fuss (Quinn-Scoggins et al, 2021). A similar pattern was also observed in individuals experiencing mental health symptoms and intimate partner violence (Ruiz et al, 2022;Yonemoto & Kawashima, 2022). Future social work research should take into account the impact of the COVID-19 pandemic on individual support seeking.…”
Section: Discussionmentioning
confidence: 85%
“…( O instrumento JBI Appraisal Tools permitiu identificar baixos riscos de vieses nos estudos selecionados, sendo cinco (17)(18)(19)21,22) considerados com qualidade elevada e três moderada. (16,20,23) Não foi possível realizar a somatória de participantes dos estudos, tendo em vista a variabilidade de sujeitos ou documentos analisados pelos autores. Quanto ao nível de evidência, de acordo com os critérios da Agency for Healthcare Research and Quality, apenas um foi classificado como nível IV (18) e os demais nível VI.…”
Section: "[All Fields] or "Ncov"[all Fields] Or "2019 Ncov"[all Field...unclassified
“…Quanto ao nível de evidência, de acordo com os critérios da Agency for Healthcare Research and Quality, apenas um foi classificado como nível IV (18) e os demais nível VI. (16,17,(19)(20)(21)(22)(23) A maioria das pesquisas foi publicada na América do Norte, (16,18,21,22) porém, em todos os textos os autores afirmam se tratar de um fenômeno global, sendo mais ou menos explícito de acordo com os valores de cada país ou cultura.…”
Section: "[All Fields] or "Ncov"[all Fields] Or "2019 Ncov"[all Field...unclassified
See 1 more Smart Citation
“…Ethnic minority women's (Nigerian) socialization from the country of birth, immigration status and acculturation influenced the disclosure and help-seeking practice in the country of immigration (Femi-Ajao, 2018). Additionally, women from minority communities such as women with disabilities (Thiara & Roy, 2022) and women from Black and Indigenous communities (Ruiz et al, 2022) may be at risk of experiencing more complexity around DV and in being able to access appropriate supportive services (Wilson et al, 2021). A recent qualitative meta-synthesis found that BME women faced additional barriers to leaving an abusive relationship because of punitive immigration laws, systemic and structural racism, cultural exclusion and in some cases, police violence (Hulley et al, 2022).…”
Section: Domestic Violence: Minority Groups Different Cultural Backgr...mentioning
confidence: 99%